PREVALENCE OF ANEMIA AND ASSOCIATED FACTORS AMONG PREGNANT WOMEN ATTENDING TRA VINH UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Anemia during pregnancy is a common health problem that may adversely affect maternal and fetal outcomes. In Tra Vinh, data on the prevalence of anemia and related factors among pregnant women remain limited.Objective: To determine the prevalence of anemia and associated factors among pregnant women attending Tra Vinh University Hospital.Subjects and methods: A descriptive cross-sectional study combined with retrospective data collection was conducted among 162 pregnant women attending Tra Vinh University Hospital from March 2024 to May 2025. Anemia was defined as hemoglobin concentration
Keywords: anemia, pregnant women, pregnancy, hemoglobin.